2009
DOI: 10.7124/bc.0007c8
|View full text |Cite
|
Sign up to set email alerts
|

Study on the putative active site of Enterococcus faecalis prolyl- tRNA synthetase editing domain by methods of site-directed mutagenesis

Abstract: The maintenance of amino acid specificity by aminoacyl-tRNA synthetases can require the hydrolysis of missynthesized products that is known as amino acid editing. Bacterial prolyl-tRNA synthetase includes a special editing domain, that deacylates alanyl-tRNAPro, and so exhibits post-transfer editing activity. The mechanism of tRNA-dependent editing by prolyl-tRNA synthetase has to be defined. The present work aim is to study the structure of the active site of enterobacteria E. faecalis prolyl-tRNA synthetase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
2
4
0
2
Order By: Relevance
“…The bacterial ProRS INS domain has been previously investigated using biochemical, 13,22,41 structural, 42 and computational studies. 22 Although there is no available crystal structure of an INS domain-tRNA complex, the computational model of E. faecalis INS bound to 5′-CCA-Ala, 22 revealed that the aminoacyl moiety binds in a well-defined hydrophobic pocket formed by residues Ile263, Val266, Ile277, and Lys279 and rationalizes the high specificity of INS for the substrate alanine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial ProRS INS domain has been previously investigated using biochemical, 13,22,41 structural, 42 and computational studies. 22 Although there is no available crystal structure of an INS domain-tRNA complex, the computational model of E. faecalis INS bound to 5′-CCA-Ala, 22 revealed that the aminoacyl moiety binds in a well-defined hydrophobic pocket formed by residues Ile263, Val266, Ile277, and Lys279 and rationalizes the high specificity of INS for the substrate alanine.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial ProRS INS domain has been previously investigated using biochemical, ,, structural, and computational studies . Although there is no available crystal structure of an INS domain-tRNA complex, the computational model of E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ïîñòòðàíñôåðíîå ðåäàêòèðîâàíèå èçó÷åíî íàìè ðàíåå ïðè ïîìîùè òåñòà íà äåàöèëèðîâàíèå àëàíèë-òÐÍÊ ÏðîÀëà [17]. Äëÿ ýòîãî ïîäîáðàíà ìóòàíòíàÿ ôîðìà ÏðîÐÑEf Ê279À, õàðàêòåðèçóþùàÿñÿ ïðàê-òè÷åñêèì îòñóòñòâèåì ïîñòòðàíñôåðíîé ðåäàêòèðóþùåé àêòèâíîñòè.…”
unclassified
“…Ýòîò ðåçóëüòàò ïðÿìî óêàçûâàåò íà ðîëü òÐÍÊ Ïðî â ãèäðîëèçå àëàíèë-àäåíèëàòà. Åãî êèíåòèêà â ïðèñóòñòâèè òÐÍÊ Ïðî ñõîäíà äëÿ äèêîãî òèïà ÏðîÐÑ è ìóòàíòíûõ ôîðì, íåñóùèõ ïîâðåaeäåííûé ðåäàêòèðóþùèé àêòèâíûé öåíòð INS-äîìåíà [17] (ðèñ. 5), ÷òî ñâèäåòåëüñòâóåò î íå-ïðè÷àñòíîñòè ìåõàíèçìà ïîñòòðàíñôåðíîãî ðåäàêòèðîâàíèÿ ê ýòîìó ïðîöåññó.…”
unclassified